Aging in a Relativistic Biological Space-Time - Maestrini, Davide; Abler, Daniel; Adhikarla, Vikram; Armenian, Saro; Branciamore, Sergio; Carlesso, Nadia; Kuo, Ya-Huei; Marcucci, Guido; Sahoo, Prativa; Rockne, Russell C. (Frontiers in Cell and Developmental Biology, 2018)
Here we present a theoretical and mathematical perspective on the process of aging. We extend the concepts of physical space and time to an abstract, mathematically-defined space, which we associate with a concept of “biological space-time” in which biological dynamics may be represented. We hypothesize that biological dynamics, represented as trajectories in biological space-time, may be used to model and study different rates of biological aging. As a consequence of this hypothesis, we show how dilation or contraction of time analogous to relativistic corrections of physical time resulting from accelerated or decelerated biological dynamics may be used to study precipitous or protracted aging. We show specific examples of how these principles may be used to model different rates of aging, with an emphasis on cancer in aging. We discuss how this theory may be tested or falsified, as well as novel concepts and implications of this theory that may improve our interpretation of biological aging.